2016
DOI: 10.15835/nsb.8.2.9792
|View full text |Cite
|
Sign up to set email alerts
|

Plankton and Macrobiota Composition and Diversity of Three Tropical Freshwaters Rivers in Ogun and Ondo States, Southwest Nigeria

Abstract: Three different rivers in Ogun and Ondo states were investigated for both micro and macro-biota of the water bodies. Several physical and chemical properties of these rivers were determined. The pH value of the studied water bodies was essentially neutral with salinity values between 0.02 -4.0‰. Microalgae communities were represented by three divisions: Cyanophyta, Bacillariophyta and Chlorophyta at Oluwa and Ifara Rivers (Ondo state), while at Ibefun River (Ogun state), five divisions: Cyanophyta, Bacillario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In general, algae of aero‐terrestrial habitats include many specific groups of algae. Accordingly, the literature on algal diversity of aero‐terrestrial habitats may be categorized into that of the Cyanobacteria (Kumar & Adhikary, 2015; Lemes‐da‐Silva et al., 2010; Pushkareva et al., 2018), Chlorophyta (Ray & Thomas, 2012; Vijayan & Ray, 2015), Bacillariophyta (Zhang et al., 2020), Streptophyta (Mikhailyuk et al., 2018), Xanthophyceae (Jimel et al., 2021; Rybalka et al., 2020), Eustigmatophyceae (Flechtner et al., 2013; Trzcińska et al., 2014), and Euglenophyceae (Adesalu & Olugbemi, 2015; Lin et al., 2013).…”
Section: Soil and Other Aero‐terrestrial Algal Diversity And Its Sign...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, algae of aero‐terrestrial habitats include many specific groups of algae. Accordingly, the literature on algal diversity of aero‐terrestrial habitats may be categorized into that of the Cyanobacteria (Kumar & Adhikary, 2015; Lemes‐da‐Silva et al., 2010; Pushkareva et al., 2018), Chlorophyta (Ray & Thomas, 2012; Vijayan & Ray, 2015), Bacillariophyta (Zhang et al., 2020), Streptophyta (Mikhailyuk et al., 2018), Xanthophyceae (Jimel et al., 2021; Rybalka et al., 2020), Eustigmatophyceae (Flechtner et al., 2013; Trzcińska et al., 2014), and Euglenophyceae (Adesalu & Olugbemi, 2015; Lin et al., 2013).…”
Section: Soil and Other Aero‐terrestrial Algal Diversity And Its Sign...mentioning
confidence: 99%
“…The authors also observed that a high diversity of algae occurred in orchards and paddy fields, whereas low diversity occurred in tea farms and sugarcane fields. In the crop fields of Nigeria, Adesalu and Olugbemi (2015) reported a high diversity of algae of the four classes Chlorophyceae, Bacillariophyceae, Euglenophyceae, and Cyanophyceae. They observed that farming practices, such as chemical fertilizers, pesticides, herbicides, and soil tillage, negatively affected algal diversity in agricultural fields.…”
Section: Soil and Other Aero‐terrestrial Algal Diversity And Its Sign...mentioning
confidence: 99%
“…Moreover, it is well-established that soil algae establish symbiotic relationships with plant roots, leading to the release of hormones that stimulate root growth [190][191][192]. This, in turn, facilitates the activities of other beneficial microorganisms associated with the plant's root system [193].…”
Section: Bacillus Cereusmentioning
confidence: 99%